Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am looking to evaluate

$$\int_0^1 x \sinh (x) \ \mathrm{dx}$$

share|improve this question
3  
integration by parts –  Will Jagy Sep 21 '12 at 2:34
add comment

4 Answers

Use integration by parts! General format:

$$\int f(x) g'(x)dx = f(x)g(x)-\int f'(x)g(x)dx$$

Remember! If you have bounds on the integral, they must be applied to the $f(x)g(x)$ part, too (this proceeds in the normal way).

So, if I recall correctly, the integral of $\sinh(x)$ is $\cosh(x)$...

So following the integration by parts formula, we see that

$\int_0^1 x\sinh(x)dx = (x\cosh(x)|_0^1 - \int_0^1 \cosh(x)dx$

$=\cosh(1)-[\sinh(1)-\sinh(0)] = \cosh(1) -\sinh(1) + \sinh(0)$

$=\cosh(1) - \sinh(1)$

I'm sure there's some tricky identity after that, but that's as far as I go.

share|improve this answer
    
well not quite a tricky identity, but $\cosh 1-\sinh 1=1/e$ immediately from their definitions –  Jonathan Sep 21 '12 at 4:48
add comment

You can also make use of the fact, that you can rewrite the integral:

$$\int_0^1 xf(x)\,\mathrm dx = \int_0^1 f(x) \int_0^x 1 \,\mathrm dy\,\mathrm dx.$$

This is just the integral over the right-angled triangle and using Fubini's theorem you arrive at $$\int_0^1 1 \int_y^1 f(x) \,\mathrm dx \,\mathrm dy.$$

Inserting $f(x) = \sinh(x)$ you get $$\int_0^1 x\sinh(x)\,\mathrm dx = \int_0^1 \int_y^1 \sinh(x)\,\mathrm dx\,\mathrm dy = \int_0^1 \cosh(1) - \cosh(y)\,\mathrm dy = \cosh(1) - \sinh(1).$$

share|improve this answer
add comment

$2\sinh(x)=e^x-e^{-x}$ and $\int e^x(f(x)+f'(x))dx=e^xf(x)$

Thus, $$2\int_0^1 x \sinh (x)dx=\int_0^1 xe^xdx-\int_0^1 xe^{-x}dx$$ $$=\int_0^1 e^x(x+1)dx-\int_0^1 e^{-x}(-x+1)d(-x)-\int_0^1 e^{x}dx+\int_0^1 e^{-x}d(-x)$$ $$=xe^x|_0^1-(-xe^{-x})|_0^1-e^x|_0^1+e^{-x}|_0^1$$ $$=e+\frac{1}{e}-(e-1)+(\frac{1}{e}-1)=\frac{2}{e}$$

Hence, $$2\int_0^1 x \sinh (x)dx=\frac{2}{e}\implies \int_0^1 x \sinh (x)dx=\frac{1}{e}$$

share|improve this answer
add comment

If you use Taylor's series representation of the integrand and then interchange the sum and integral, you simply get

$$\sum_{k=0}^{\infty} \left(\frac{1}{(2k+2)!}-\frac{1}{(2k+3)!}\right) = \frac{1}{e}.$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.